Becoming scientific-environmental citizens through citizen science in China - Goron, C; Lora-Wainwright, A; Huang, S (SAGE Publications, 2024)
This article advocates for a closer study of the forms of citizenship nurtured among individual participants in citizen science (CS) projects by highlighting some salient features of CS in China. Through a detailed examination of the experiences of students participating in the CS activities of a Chinese environmental NGO, it proposes that attention to CS as a means of democratizing science should be complemented by a similar attention to the ways in which CS fosters “scientific-environmental citizenship.” The article argues that these emergent forms of citizenship may be revealed by focusing on the experiences, perspectives, values and skills acquired by participants, and the specific polity in which CS initiatives are situated. This attention to the development of scientific-environmental citizenship as an outcome of CS is particularly valuable in contexts where democratic participation is otherwise constrained, but also yields a more nuanced understanding of citizenship enacted through CS in democratic contexts.